The Role of Cu 2+ Concentration in Luminescence Quenching of Eu 3+ / Cu 2+ Co-doped ZrO2 Nanoparticles - Pham Hung, Vuong; Van Huan, Pham; Dinh Tam, Phuong; Thi Ha Hanh, Nguyen; Xuan Thang, Cao (VNU Journal of Science: Mathematics - Physics; Vol 35 No 1, 2019)
Abstract: This paper the role of Cu 2+ concentrations in luminescence quenching of Eu 3+ / Cu 2+ doped ZrO 2 nanoparticles synthesized by co-precipitation method. The synthesized Eu 3+ / Cu 2+ doped ZrO 2 nanoparticles were observed to have sphere morphology with a diameter of ~ 25 nm. The XRD patterns of the nanoparticles revealed the peaks that were to be crystalline tetragonal ZrO 2 . The addition of Cu 2+ to the Eu 3+ doped ZrO 2 nanoparticles resulted in a significant suppress luminescence in Eu 3+ / Cu 2+ doped ZrO 2 nanoparticles, which was attributed to the spectral overlap occurs between Cu 2+ absorption and Eu 3+ emission ( 5 D 0 → 7 F 2 transition). Keywords: Zirconia; luminescence; precipitation; quenching, nanoparticles.